Du pavé bâti au pavé battu : les mobilisations des usagers pour les infrastructures de voirie et leur prise en compte politique, Lyon, années 1950-1970 - Louis Baldasseroni (Métropoles)
The street is a well-known medium of expression for humanities. It also poses the issue of mobilisation by its road infrastructures: demands, complaints and oppositions vary widely, from simple requests for pedestrian crossings, to oppositions to major infrastructure projects. The territory of everyday life, the streets evolved as an important, unifying factor of mobilisation since the end of the 19th century and seem to be declining as a framework for claims from the 1960s onwards. This is due to diversification, demands and actions of mobilised actors, which public authorities have difficulty integrating into the customary frameworks. However, some streets are subject to opposition to public action and policies, becoming areas of action and conflict during the 1970s. Now, requests directly addressed to urban road services concern minor infrastructure improvements such as traffic lights or pedestrian crossings.